Functional autonomy, bone mineral density and risk of falls in older women with two distinct body composition profiles - Lucio Flávio Gomes Ribeiro da Costa; Elizabeth Carvalho Lugão; Karollyni Bastos Andrade Dantas; Matthew T Corey; Rodrigo Gomes de Souza Vale; Claudia Moura Melo; Estelio Henrique Martin Dantas (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objetive: Evaluate the functional autonomy, bone mineral density and risk of falling in older women of two different body composition profiles.